Decreased Reactivity of Skin Microcirculation in Response to l-Arginine in Later-Onset Type 1 Diabetes - Neubauer-Geryk, Jolanta (American Diabetes Association, 2013)
OBJECTIVE: The aim of our study was to evaluate the vasodilatory effect of l-arginine infusion on the skin microcirculation and to assess the relationship between this effect and the presence of microangiopathy in patients with type 1 diabetes. RESEARCH DESIGN AND METHODS: Capillaroscopy was performed before and after l-arginine infusion in 48 diabetic patients (26 women and 22 men; age, 39.8 ± 6.3 years) and 24 volunteers free of any chronic disease (13 women and 11 men; age, 38.0 ± 6.7 years). The skin microcirculation reactivity, as expressed by the percentage of area covered by capillaries (coverage) and the distance between capillaries (distance), and the relationship between microcirculation reactivity and the presence of microangiopathic complications were assessed. RESULTS: The distance before l-arginine infusion was significantly lower in patients than in controls (221 [153–311] vs. 240 [185–356] µm; P = 0.02) and did not differ after l-arginine infusion (223.5 [127–318] vs. 242.5 [181–341] µm; P = 0.27). The difference between the coverage values obtained before and after l-arginine infusion (Δcoverage) was significantly different from zero in the control group but not in the diabetes group. Patients with later onset of diabetes were characterized by decreased skin microcirculation reactivity when compared with patients with earlier onset of diabetes (−1.18 [−5.07 to 11.60] vs. 1.36 [−6.00 to 8.06]; P = 0.02) despite the higher prevalence of retinopathy in patients with earlier onset of diabetes (64% vs. 26%; P = 0.02). CONCLUSIONS: Skin microvascular reactivity is impaired in patients with later onset of type 1 diabetes. Capillaroscopy with l-arginine infusion is useful for the identification of skin microangiopathy in type 1 diabetes.